A Gentle Occupation : Dutch Military Operations in Iraq, 2003-2005 - Cate, Arthur ten; Brocades Zaalberg, Thijs (Book collections on Project MUSE., 2014)
This book analyses the way Dutch forces conducted military stabilization operations in the aftermath of the 2003 U.S.-led invasion in Iraq. It looks at why, in contrast to most allied troops elsewhere in Iraq, Dutch forces in Al Muthanna province met with little resistance and left Iraq self-confident of their ability to deal with this type of military operation. On the basis of extensive archival research and interviews, the authors examine the way the Dutch government consciously framed this mission as different from the American and British occupation and often in contrast to the actual situation on the ground. Furthermore, they unravel the widespread idea of a unique and more effective 'Dutch approach', by dealing with the Dutch case in detail and by subsequently examining it in the context of the Coalition Forces' experiences. In the end, they argue that despite effective tactical reflexes by battle group commanders, stability in Al Muthanna was first and foremost conditions-driven rather than the result of a unique approach by Dutch military forces.